Interactions between workers and the technology of production: evidence from professional baseball - Eric D. Gould; Eyal Winter (Institute for the Study of Labor (IZA), 2007)
This paper examines how the effort choices of workers within the same firm interact with each other. In contrast to the existing literature, we show that workers can affect the productivity of their co-workers based on income maximization considerations, rather than relying on behavioral considerations such as peer pressure, social norms, and shame. Theoretically, we show that a worker's effort has a positive effect on the effort of co-workers if they are complements in production, and a negative effect if they are substitutes. The theory is tested using panel data on the performance of baseball players from 1970 to 2003. The empirical analysis shows that a player's batting average significantly increases with the batting performance of his peers, but decreases with the quality of the team's pitching. Furthermore, a pitcher's performance increases with the pitching quality of his teammates, but is unaffected by the batting output of the team. These results are inconsistent with behavioral explanations which predict that shirking by any kind of worker will increase shirking by all fellow workers. The results are consistent with the idea that the effort choices of workers interact in ways that are dependent on the technology of production. These findings are robust to controlling for individual fixed-effects, and to using changes in the composition of one's co-workers in order to produce exogenous variation in the performance of one's peers.
Keywords: 330; Peer effects; team production; externalities; Arbeiter; Leistungsmotivation; Verhaltensökonomik; Gruppenarbeit; Fertigungsorganisation; Theorie; Professioneller Sport; Schätzung; USA